An autonomous target tracking system for the offshore drone rescue system - Zhang, MingCheng (Nanyang Technological University, 2020)
The purpose of this research report is to describe a way to increase survivability for survivors after a shipwrecking of an ocean-going ship in warm oceans. A drone together with a camera and Kalman Filter algorithm is used to carry out this task. According to the simulation result, the desired purpose is achieved, and some future developments are also proposed to improve on the project.